Wellbore integrity evaluation method considering changes in casing size and cement sheath properties after CO2 corrosion

By conducting multi-factor orthogonal tests and dynamic corrosion experiments under CO2 corrosion environment, the mechanical parameters of the casing and cement ring were measured, and combined with the Mori-Tanaka mechanical model and finite element numerical simulation, a casing-cement stone combination mechanical model was established, which solved the error problem of the mechanical integrity evaluation of the wellbore in the existing technology, and improved the accuracy and safety of the prediction.

CN118774734BActive Publication Date: 2025-04-18NORTHEAST GASOLINEEUM UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410923611.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-10
Publication Date
2025-04-18
Estimated Expiration
2044-07-10

AI Technical Summary

Technical Problem

The prior art lacks a wellbore mechanical integrity evaluation method that takes into account the reduction of casing wall thickness and changes in cement ring material strength and elastic modulus in the CO2 corrosion environment, resulting in large errors between the prediction results and the actual situation.

Method used

The mechanical parameters of the casing and cement ring after corrosion were determined using multi-factor orthogonal test method and CO2 dynamic corrosion experiment. Combined with the Mori-Tanaka mechanical model and finite element numerical simulation, a combined mechanical model of casing-cement stone uncorroded layer-cement stone corrosion layer-formation corrosion layer-wellbore integrity evaluation was established.

Benefits of technology

By considering the changes in the dimensions and mechanical parameters of the casing and cement ring after CO2 corrosion, the accuracy of the prediction of wellbore integrity is improved, the error between the prediction results and actual working conditions is reduced, and the cost of well repair is saved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118774734B_ABST
    Figure CN118774734B_ABST
Patent Text Reader

Abstract

The present invention relates to the consideration of CO 2 A method for evaluating wellbore integrity based on the changes in casing size and cement sheath performance after corrosion, which includes: 2 Before dynamic corrosion, the mechanical parameters of cement paste were measured, and corrosion experiments were carried out according to the preset corrosion time. Nanoindentation experiments were carried out in the corrosion area of ​​cement paste to calculate the elastic modulus and Poisson's ratio of the test material. E r ; Upgrade the elastic modulus and Poisson's ratio parameters of micro / nano scale to macro scale; clean and dry the corroded casing coupons, weigh them to get the mass of the corroded coupons, calculate the corrosion rate, and establish the corrosion rate of casing pipes under the influence of temperature and CO2 partial pressure over time; respectively establish the corrosion rate of casing pipes under the influence of temperature and CO2 partial pressure 2 A mathematical model for the change of elastic modulus and Poisson's ratio of cement paste with corrosion time under the influence of partial pressure factors; a mechanical model of the assembly is established; and the failure form of the wellbore integrity is judged based on the numerical simulation results. The present invention realizes the prediction and evaluation of the integrity of CCUS wellbore under corrosion conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The present invention relates to CO 2 Oil recovery and CO 2 CO backflow from flooding production wells 2 A method for evaluating the mechanical integrity of a wellbore under conditions of CO 2 Wellbore integrity evaluation method based on changes in casing size and cement sheath properties after corrosion. Background technology:

[0002] Carbon capture, utilization and storage (CCUS) technology is one of the important technical means for my country to achieve its dual carbon goals. Compared with the previous carbon capture and storage technology (CCS), CCUS uses carbon dioxide to flood oil to achieve supercritical carbon dioxide (SC-CO 2 ) Fracturing transformation of unconventional reservoirs, CO 2 The simultaneous geological storage of carbon dioxide during oil recovery (EOR) is one of the most cost-effective methods among many feasible energy conservation and emission reduction solutions. CCUS technology captures carbon dioxide from different sources and injects it into deep formations (depleted or abandoned oil and gas reservoirs, deep saline formations, etc.), providing a new way to achieve CO 2 The effectiveness of the storage must meet the requirement that the annual leakage does not exceed 0.01%, ensuring that the CO 2 The wellbore is a direct channel connecting the ground and the underground storage area. Therefore, the integrity of the wellbore is the key to the CO 2 The key to safe storage. In the long-term storage process, due to the 2 Soluble in water, acidic, CO 2 It will corrode the wellbore barrier materials (oil pipes, casings, cement rings, etc.), induce the thinning of the oil casing wall thickness, and the damage and degradation of the material strength, elastic modulus, porosity and permeability, etc., which will lead to the failure of the wellbore structure integrity. In severe cases, it is easy to cause accidents such as blowouts, resulting in a decrease in oil well production or even shutdown, seriously affecting the normal production of the oil field. At the same time, with the continuous increase in costs caused by blind and frequent well repairs, the development cost has risen.

[0003] At present, the mechanical integrity analysis of casing-cement sheath-formation combination wellbore is mostly analyzed and evaluated by numerical simulation methods. Among them, Lian Zhanghua, Li Jun and others conducted mechanical analysis on the structure of casing-cement sheath-formation combination. According to different casing pressure test values ​​and ground stress loading states, the mechanical analysis method of the combination was established based on elastic mechanics theory or finite element theory. Yin Youquan, Fang Jun and other scholars took the casing-cement sheath-formation combination as their research target. Based on elastic mechanics, they analyzed the stress characteristics of casing and cement sheath under the action of uniform internal pressure and non-uniform ground stress under ideal conditions, and obtained the surface force distribution and internal stress distribution of casing and cement sheath under different ground stresses, and analyzed and calculated the influence of various parameter changes (such as: cement sheath elastic modulus and Poisson's ratio, casing thickness, cement sheath and casing contact conditions, etc.) on the stress distribution of casing and cement sheath. Zeng Dezhi, Lin Yuanhua and other scholars studied the elastic mechanics model of casing-cement sheath-casing combination under non-uniform ground stress to study the stress and failure of cement sheath. They gave the stress-strain and displacement calculation formulas of casing and cement sheath, and analyzed the stress distribution of cement sheath bonding interface under non-uniform ground stress. The results show that under non-uniform ground stress, the stress distribution law of cement sheath bonding interface shows non-uniformity, which will cause the cement sheath bonding surface to be damaged before the cement sheath body or casing, thereby accelerating the damage of casing. Li Jun, Chen Mian and other scholars established the mechanical distribution model of casing-cement sheath-stratum combination by studying the theory of multi-layer combined thick-walled cylinder, and conducted an elastic-plastic analysis of the whole combination under uniform ground stress. The stress-strain distribution expression of casing-cement sheath-stratum combination under elastic-plastic mechanical conditions was obtained, and the stress characteristics of the combination under different parameters such as complete plasticity and linear elasticity were analyzed. The influence of the elastic modulus of cement sheath on the external squeeze load of casing under different formation property parameters was explained, and the plastic limit problem of the combination was studied. Zhang Zhi et al. used CO 2 Taking the huff and puff well as an example, a wellbore integrity optimization method based on wellbore tubing corrosion and operating loads was proposed, and the wellbore integrity life and failure-sensitive areas were determined, providing guidance for extending the service life of old wells and establishing a scientific and effective management system.

[0004] In summary, for CO 2 The numerical simulation evaluation method for the mechanical integrity of the casing-cement sheath-formation assembly under corrosive environment mainly has the following problems:

[0005] 1. The existing numerical simulation evaluation method for the mechanical integrity of the casing-cement sheath-formation combination lacks the consideration of long-term CO 2 The corrosive environment affects the casing wall thickness, resulting in dimensional changes, cement sheath material strength, elastic modulus and other mechanical parameters. 2Due to the influence of corrosion, the casing wall thickness will be reduced, resulting in a decrease in pressure bearing capacity; the cement sheath is affected by saturated carbonated water at the contact point with the formation, causing a corrosion layer to appear on the cement sheath, and the mechanical parameters of the corrosion layer, such as the elastic modulus and Poisson's ratio, will change significantly.

[0006] 2. Existing CO 2 The mechanical parameters of the corroded cement sheath body are all the overall change values ​​after corrosion, and no distinction is made between the corroded area and the non-corroded area. 2 The corrosion of cement paste will produce obvious zoning between corroded and uncorroded areas. The mechanical parameters of the corroded area vary greatly, and there is a lack of mechanical parameter measurement methods for the corroded area.

[0007] 3. The existing mechanical models of casing-cement sheath-stratum combination are all three-layer structures, which lack consideration of CO 2 The corrosion layer appears in the corroded cement sheath, and the mechanical parameters of the corrosion area have a great influence on the mechanical integrity of the assembly, so the corrosion layer needs to be considered.

[0008] The problems with the above-mentioned wellbore integrity evaluation methods lead to large errors in the prediction and evaluation of wellbore integrity under long-term storage conditions in CCUS projects during actual production, increasing production risks and maintenance costs. Therefore, a wellbore integrity prediction and evaluation method suitable for carbon dioxide environments is urgently needed to reduce the error between the prediction results and actual production conditions, and effectively save the development costs caused by well repairs. Summary of the invention:

[0009] The object of the present invention is to provide a method for 2 Wellbore integrity evaluation method based on the change of casing size and cement sheath performance after corrosion. 2 The wellbore integrity evaluation method based on the change of casing size and cement sheath performance after corrosion is used to solve the problem that the wellbore integrity evaluation prediction and evaluation results in the prior art have large errors compared with the actual situation.

[0010] The technical solution adopted by the present invention to solve the technical problem is: 2 The wellbore integrity evaluation method for the changes in casing size and cement sheath performance after corrosion includes the following steps:

[0011] Step 1: Indoor test adopts multi-factor orthogonal test method to determine the influencing factors based on the data provided on site. The influencing factors include temperature, CO 2 Partial pressure, formation water Cl - concentration, flow rate, establish an orthogonal matrix, and conduct N experiments;

[0012] Step 2: Perform CO 2Before dynamic corrosion, the mechanical parameters of cement paste were measured, including initial compressive strength, elastic modulus, and Poisson's ratio. The initial mass of the casing hanger was obtained by weighing the casing hanger. 1 ; Place cement stone and weighed casing hanger into CO 2 In the dynamic corrosion instrument, the water content is calculated according to the liquid-gas ratio of the gas produced on site, and corrosion experiments are carried out according to the preset corrosion time;

[0013] Step 3: After the predetermined corrosion time is reached, 2 The dynamic corrosion instrument is cooled and depressurized, and the cement stone and casing hanging pieces in the kettle are taken out. The residual moisture on the surface of the hanging pieces is absorbed with absorbent paper, and they are put into the experimental storage bag one by one.

[0014] Step 4: Carry out nano-indentation test on cement stone corrosion area, and calculate the elastic modulus and Poisson's ratio of the test material through the load-displacement curve obtained by the indentation test. r Obtained from the load-displacement curve;

[0015] Step 5: Use the Mori-Tanaka mechanical model to achieve scale upgrade, and upgrade the elastic modulus and Poisson's ratio parameters at the micro / nano scale to the macro scale;

[0016] Step 6: Clean and dry the corroded casing coupons, and weigh them to obtain the mass G of the corroded coupons. 2 , and calculate the corrosion rate; the orthogonal test data of casing hanging corrosion rate are used, and the mathematical method of multiple regression is used to establish the corrosion rate of casing pipes changing with time under the influence of temperature and CO2 partial pressure:

[0017] V cor =Y·a·t b (9)

[0018] In the formula, a and b are the corrosion temperature T and CO 2 Molar concentration C (CO2) Equal factors function;

[0019] Calculate the residual strength of uniform corrosion, for wall thickness δ, yield strength σ y The column, after corrosion time t:

[0020] Remaining wall thickness of the pipe, i.e. size: δ t =δ-v t t (10)

[0021] Residual tensile strength of pipe string: T o =πσ y [R 2 -(r+v t t) 2 ] / 4 (11)

[0022] Residual internal pressure resistance of pipe string: p bo =2σ y (δ-v t t) / R (12)

[0023] Residual collapse strength of pipe string: p co =2σ y [R / (δ-v t t)-1] / [R / (δ-v t t)] 2 (13)

[0024] Where: T o —Residual tensile strength of the pipe string, kN; P bo —Residual internal pressure strength of the pipe string, MPa; P co —residual collapse strength of the pipe string, MPa; t—corrosion time, a; σ y — pipe string yield strength, MPa; R—original pipe string outer diameter, mm; r—original pipe string inner diameter, mm; δ—original pipe string wall thickness, mm; v t —Corrosion rate, mm / a;

[0025] Step 7: Use the mathematical method of multiple regression to establish the influence of temperature, CO 2 Mathematical model of the change of elastic modulus and Poisson's ratio of cement paste with corrosion time under the influence of partial pressure factors;

[0026] Step 8: Consider CO 2 The phenomenon of corrosion layer after cement stone corrosion is considered, and a mechanical model of casing-cement stone uncorroded layer-cement stone corrosion layer-stratum combination is established;

[0027] Step 9: Based on the numerical simulation results, the failure mode of wellbore integrity is determined. When the tangential stress on the cement sheath is greater than its tensile strength, the cement sheath undergoes tensile failure. When the equivalent stress on the cement sheath is greater than its compressive strength, the cement sheath fails. The tensile failure of cement paste depends on the circumferential stress state of the cement sheath, and the failure criterion is shown in formula (16). The compressive failure of cement paste depends on the radial stress state of the cement sheath, and the failure criterion is shown in formula (17). Based on the distortion energy theory, i.e., the fourth strength theory, the yield failure criteria of cement sheath and casing are shown in formulas (18) and (19). According to the three determination methods, the wellbore integrity failure forms are divided into cement sheath tensile failure, cement sheath compression failure, cement sheath yield failure, and casing yield failure.

[0028] σ θ ≥σ t (16)

[0029] σ r ≥σ c (17)

[0030] σ M ≤σ s (18)

[0031]

[0032] Where: t —Tensile strength of cement sheath, MPa; σ s — allowable stress of material determined by tensile test, MPa; σ M —Equivalent stress, MPa.

[0033] Step 1 in the above scheme is as follows: Indoor test adopts multi-factor orthogonal test method, and determines the influencing factors according to the data provided on site, including temperature, CO 2 Partial pressure, formation water Cl - concentration and flow rate, an orthogonal matrix was established, and a total of N tests were conducted; the materials used in the test were casing pipes and cement ash provided on site in the oil field; the cement stone was prepared in accordance with GB / T19139-2012 Test Method for Oil Well Cement, and the cement stone sample was taken out after curing for 7 days, cleaned and sealed in anhydrous ethanol for standby use; the casing pipe was obtained by turning and milling, and the casing hanging piece was gradually polished with 200-1000# emery paper to achieve a mirror state, and then cleaned with deionized water and anhydrous alcohol in turn, and placed in a vacuum drying oven for standby use.

[0034] Step 2 in the above scheme is specifically: CO 2 Before dynamic corrosion, the initial mechanical parameters of the spare cement stone were measured using a uniaxial tension and compression testing machine. The initial mechanical parameters included compressive strength, elastic modulus, and Poisson's ratio. The casing hanger was weighed using a 0.1 mg electronic balance to obtain an initial mass of G. 1 ; Place the prepared cement stone and weighed casing hanger into CO 2 In the dynamic corrosion instrument, the water content is calculated according to the liquid-gas ratio of the gas produced on site, and the prepared Cl-containing - Formation water; CO 2 The dynamic corrosion instrument is heated and CO 2 The air in the kettle was removed for 5 minutes, and CO with different partial pressures was injected. 2 The gas flow rate controller of the fluid in the kettle was turned on, and corrosion experiments were carried out for 3d, 5d, 7d and 15d respectively according to the preset corrosion time.

[0035] Step 4 in the above scheme is as follows: nanoindentation experiment of cement stone corrosion area is carried out using G200X micro-nanomechanical testing platform. The radius of the calibrated Berkovich diamond indenter is less than 20nm, and the effective indentation depth is greater than 30μm. In the standard indentation test mode, a constant indentation strain rate of 0.05s is used during loading. -1 The load-holding stage lasts for 60 seconds, and the rate of the unloading stage is kept the same as the indentation rate of the loading stage. The typical load-displacement curve obtained by the indentation test is used to calculate the elastic modulus and Poisson's ratio of the test material according to the Oliver-Pharr (OP) method, according to formula (1); E r Obtained from the load-displacement curve, according to formulas (2) and (3):

[0036]

[0037] Where: E—elastic modulus of the test material, GPa; v—Poisson’s ratio of the test material, dimensionless; E r —Elastic modulus test value, GPa; E i —Elastic modulus of the indenter, which is 1411 GPa; v i —Poisson’s ratio of the indenter, dimensionless, with a value of 0.07; the elastic modulus test value is a comprehensive reflection of the elastic modulus of the indenter and the test material; S—contact stiffness, mN / nm, equal to the slope of the initial unloading curve; β—indenter shape correlation coefficient, dimensionless, the Berkovich indenter is generally taken as 1.034; A—indenter contact area, nm 2 , determined by pressure head calibration; P—load, mN; h—pressure depth, nm; h max —Maximum penetration depth of loading section, nm.

[0038] The mechanical model in step 5 of the above scheme is as follows:

[0039]

[0040] Among them, K hom —Shear modulus (unit: Pa); f r —Volume fraction of different mineral particles (unit: %), r = 0, 1, 2; f s —Volume fraction of s phase (unit: %), s = 0, 1; k r — Bulk modulus of different mineral particles (unit: Pa); k s —The proportion of clay minerals (unit: %); μ 0 is the equivalent shear modulus of low-strength minerals (unit: Pa); G hom —bulk modulus (unit: Pa); μ r —Shear modulus of different mineral particles (unit: Pa); k 0—Equivalent bulk modulus of low-strength minerals (unit: Pa); μ s —Shear modulus of clay minerals (unit: Pa); E hom —Young's modulus after scale upgrade (unit: Pa); ν hom —Dimensionless Poisson’s ratio after scaling.

[0041] In the above scheme, step 7 is affected by temperature, CO 2 The mathematical model of the change of cement paste elastic modulus and Poisson's ratio with corrosion time under the influence of partial pressure factors is as follows:

[0042]

[0043] In the formula, a i , b i For the corrosion temperature T, CO 2 Molar concentration C (CO2) Equal factors function.

[0044] Beneficial effects:

[0045] 1. The evaluation method of the present invention realizes the 2 Under corrosive conditions, the casing corrosion rate, the residual strength variation law caused by the change of wall thickness over time, the elastic modulus of cement sheath, Poisson's ratio and other mechanical parameters over time; make up for the CO 2 Corrosion situation, the existing mechanical model of casing-cement sheath-formation combination is not applicable.

[0046] 2. The evaluation method of the present invention realizes the determination of mechanical parameters such as micro elastic modulus and Poisson's ratio of cement stone after corrosion by nanoindentation technology, and uses the Mori-Tanaka mechanical model for scale upgrading, which makes up for the lack of direct determination of mechanical parameters of cement sheath corrosion area in existing test methods.

[0047] 3. The evaluation method of the present invention realizes the evaluation of the underground CO by adding the cement sheath corrosion layer to the existing mechanical model of the casing-cement sheath-formation combination, that is, the mechanical model of the casing-cement stone uncorroded layer-cement stone corroded layer-formation combination. 2 Direct characterization of the corrosion area, combined with the prediction data of casing and cement sheath mechanical parameters, enables mechanical integrity evaluation and analysis of CCUS wellbore during long-term operation.

[0048] 4. The evaluation method of the present invention has a simple operation process and is suitable for the actual production process of CO2 in CCUS projects. 2 The method is novel and highly practical for complex working conditions such as corrosive environments, and has high accuracy in predicting and determining the failure time of wellbore mechanical integrity.

[0049] 5. The present invention meets the requirements of CCUS project CO 2 The actual structural condition after corrosion of casing and cement ring, considering the dimensional change caused by the thinning of casing wall thickness and the cement stone in CO 2 The corrosion rate and mechanical parameter changes with time under corrosive conditions improve the accuracy of the prediction and evaluation of the actual wellbore corrosion conditions and safe service life on site. This method is novel, has a simple operation process and is practical. It can provide a reference for the wellbore integrity evaluation and safe operation life prediction of CCUS projects on site in oil fields.

[0050] 6. The present invention adopts the corrosion data results obtained based on indoor tests combined with finite element numerical simulation technology to realize the integrity prediction and evaluation method of CCUS wellbore under corrosion conditions. Description of the drawings:

[0051] Figure 1 It is a schematic diagram of the mechanical model of the combination in the present invention.

[0052] In the figure: 1 casing 2 cement sheath uncorroded layer 3 cement sheath corroded layer 4 formation. Specific implementation method:

[0053] The present invention will be further described below:

[0054] This consideration of CO 2 Wellbore integrity evaluation method based on casing size and cement sheath performance changes after corrosion

[0055] Step 1: The indoor test uses a multi-factor orthogonal test method to determine the temperature, CO 2 Partial pressure, formation water Cl - n influencing factors such as concentration and flow rate were considered, an orthogonal matrix was established, and a total of N experiments were conducted. The materials used in the experiment were casing pipes and cement ash provided on site in the oil field. The cement stone was prepared according to GB / T 19139-2012 Test Method for Oil Well Cement to obtain a 25mm diameter * 50mm high cylinder. After curing for 7 days, the cement stone sample was taken out, cleaned and sealed in anhydrous ethanol for standby use; the casing pipe was milled to obtain a 50mm*15mm*5mm hanging piece specimen, and the surface of the specimen was gradually polished to a mirror state using 200~1000# emery paper, and then cleaned with deionized water and anhydrous alcohol in turn, and placed in a vacuum drying oven for standby use.

[0056] Step 2: Perform CO 2 Before dynamic corrosion, the initial compressive strength, elastic modulus, Poisson's ratio and other mechanical parameters of the standby cement stone were measured using a uniaxial tension and compression testing machine. The standby hanging piece was weighed using a 0.1 mg electronic balance to obtain an initial mass of G. 1Put the prepared cement stone and weighed casing hanger into CO 2 In the dynamic corrosion instrument, the water content is calculated according to the liquid-gas ratio of the gas produced on site, and the prepared Cl-containing - Formation water. CO 2 The dynamic corrosion instrument is heated and CO 2 The air in the kettle was removed for 5 minutes, and CO with different partial pressures was injected. 2 The process of gas and opening the flow rate controller of the fluid in the kettle is carried out, and corrosion experiments are carried out for 3d, 5d, 7d, 15d, etc. according to the preset corrosion time.

[0057] Step 3: After the predetermined corrosion time is reached, 2 The dynamic corrosion instrument is cooled and depressurized, and the cement stone and casing hanging pieces in the kettle are taken out. The residual moisture on the surface of the hanging pieces is absorbed with absorbent paper, and they are placed into experimental preservation bags one by one.

[0058] Step 4: Use the G200X micro-nanomechanical testing platform to carry out nanoindentation experiments on cement stone corrosion areas. The radius of the calibrated Berkovich diamond indenter is less than 20nm, and the effective indentation depth is greater than 30μm. In the standard indentation test mode, a constant indentation strain rate of 0.05s is used during the loading process. -1 The load holding stage lasts for 60 seconds, and the rate of the unloading stage is kept the same as the indentation rate of the loading stage. The typical load-displacement curve obtained by the indentation test can be used to calculate the elastic modulus and Poisson's ratio of the test material according to the Oliver-Pharr (OP) method, see formula (1). r It can be obtained from the load-displacement curve, see equations (2) and (3).

[0059]

[0060] Where: E—elastic modulus of the test material, GPa; v—Poisson’s ratio of the test material, dimensionless; E r —Elastic modulus test value, GPa; E i —Elastic modulus of the indenter, which is 1411 GPa; v i —Poisson’s ratio of the indenter, dimensionless, valued at 0.07; the elastic modulus test value is a comprehensive reflection of the elastic modulus of the indenter and the test material. S—contact stiffness, mN / nm, equal to the slope of the initial unloading curve; β—indenter shape correlation coefficient, dimensionless, the Berkovich indenter is generally taken as 1.034; A—indenter contact area, nm 2 , determined by pressure head calibration; P—load, mN; h—pressure depth, nm; h max —Maximum penetration depth of loading section, nm.

[0061] Step 5: Use the Mori-Tanaka mechanical model to achieve scale upgrade, and upgrade the elastic modulus, Poisson's ratio and other parameters of the small scale (micro / nano scale) to the macro scale. The mechanical model is shown in formula (4) to formula (7).

[0062]

[0063] Among them, K hom —Shear modulus (unit: Pa); f r —Volume fraction of different mineral particles (unit: %), r = 0, 1, 2; f s —Volume fraction of s phase (unit: %), s = 0, 1; k r — Bulk modulus of different mineral particles (unit: Pa); k s —The proportion of clay minerals (unit: %); μ 0 is the equivalent shear modulus of low-strength minerals (unit: Pa); G hom —bulk modulus (unit: Pa); μ r —Shear modulus of different mineral particles (unit: Pa); k 0 —Equivalent bulk modulus of low-strength minerals (unit: Pa); μ s —Shear modulus of clay minerals (unit: Pa); E hom —Young's modulus after scale upgrade (unit: Pa); ν hom —Dimensionless Poisson’s ratio after scaling.

[0064] Step 6: Rinse the surface of the corroded casing coupon sample with distilled water to remove corrosion residues, remove water with anhydrous alcohol and dry. After removing the corrosion product film, weigh it with an electronic balance with an accuracy of 0.1 mg to obtain the mass G of the corroded coupon. 2 , the corrosion rate is calculated using formula (8).

[0065]

[0066] Where V cor —Average corrosion rate, mm / a; ΔG—weight loss of sample (G 1 -G 2 ), kg; ρ—density of the material, kg / m 3 , S—contact area, m 2 , t—test time, d.

[0067] The orthogonal test data of casing hanger corrosion rate are used to establish the corrosion rate of casing pipes changing with time under the influence of temperature, CO2 partial pressure and other factors, see formula (9).

[0068] V cor=Y·a·t b (9) In the formula, a and b are the corrosion temperature T and CO 2 Molar concentration C (CO2) Equal factors function.

[0069] According to API TR 5C3 standard, the uniform corrosion residual strength is calculated for wall thickness δ and yield strength σ y The column, after corrosion time t:

[0070] Remaining wall thickness of the pipe, i.e. size:

[0071] δ t =δ-v t t (10)

[0072] Residual tensile strength of pipe string:

[0073] T o =πσ y [R 2 -(r+v t t) 2 ] / 4 (11)

[0074] Residual internal pressure strength of pipe string:

[0075] p bo =2σ y (δ-v t t) / R (12)

[0076] Residual collapse strength of pipe string:

[0077] p co =2σ y [R / (δ-v t t)-1] / [R / (δ-v t t)] 2 (13) Where: T o —Residual tensile strength of the pipe string, kN; P bo —Residual internal pressure strength of the pipe string, MPa; P co —residual collapse strength of the pipe string, MPa; t—corrosion time, a; σ y — pipe string yield strength, MPa; R—original pipe string outer diameter, mm; r—original pipe string inner diameter, mm; δ—original pipe string wall thickness, mm; v t —Corrosion rate, mm / a.

[0078] Step 7: Similarly, use the mathematical method of multiple regression to establish the temperature, CO 2 The mathematical models for the changes of the elastic modulus and Poisson's ratio of cement paste with corrosion time under the influence of partial pressure and other influencing factors are shown in formulas (14) and (15).

[0079]

[0080] In the formula, a i , b i For the corrosion temperature T, CO 2 Molar concentration C (CO2) Equal factors function.

[0081] Step 8: Consider CO 2 The phenomenon of corrosion layer after corrosion of cement stone is established. Figure 1 The mechanical model of the casing-cement uncorroded layer-cement corroded layer-stratum combination is shown in the figure. The outside of casing 1 is cement uncorroded layer 2, and the outside of cement uncorroded layer 2 is cement corroded layer 3. Casing 1, cement uncorroded layer 2 and cement corroded layer 3 are in stratum 4. The mechanical parameters of cement and casing used in the simulation are the initial indoor test data in the above steps and the established temperature, CO 2 The data are calculated based on a mathematical model of multiple factors such as partial pressure, and the formation data are obtained from actual field data.

[0082] Step 9: Based on the numerical simulation results, the failure mode of wellbore integrity is determined. When the tangential stress on the cement sheath is greater than its tensile strength, the cement sheath undergoes tensile failure. When the equivalent stress on the cement sheath is greater than its compressive strength, the cement sheath fails. The tensile failure of cement paste depends on the circumferential stress state of the cement sheath, and the failure criterion is shown in formula (16). The compressive failure of cement paste depends on the radial stress state of the cement sheath, and the failure criterion is shown in formula (17). Based on the distortion energy theory, i.e., the fourth strength theory, the yield failure criteria of cement sheath and casing are shown in formulas (18) and (19). According to the three determination methods, the wellbore integrity failure forms are divided into cement sheath tensile failure, cement sheath compression failure, cement sheath yield failure, and casing yield failure.

[0083] σ θ ≥σ t (16)

[0084] σ r ≥σ c (17)

[0085] σ M ≤σ s (18)

[0086]

[0087] Where: t —Tensile strength of cement sheath, MPa; σ s — allowable stress of material determined by tensile test, MPa; σ M —Equivalent stress, MPa.

Claims

1. A method for evaluating wellbore integrity considering the changes in casing size and cement sheath performance after CO2 corrosion, characterized in that The steps include: Step 1: Indoor test uses multi-factor orthogonal test method to determine the influencing factors based on the data provided on site. The influencing factors include temperature, CO2 partial pressure, formation water Cl - concentration, flow rate, establish an orthogonal matrix, and conduct N experiments; Step 2: Before the CO2 dynamic corrosion, the mechanical parameters of the cement stone are measured, including the initial compressive strength, elastic modulus, and Poisson's ratio. The casing hanger is weighed to obtain the initial mass G1; the cement stone and the weighed casing hanger are placed in the CO2 dynamic corrosion instrument, and the water content is calculated according to the liquid-gas ratio of the on-site produced gas, and the corrosion experiment is carried out according to the preset corrosion time; Step 3: After the predetermined corrosion time is reached, the CO2 dynamic corrosion instrument is cooled and depressurized, the cement stone and casing hanging pieces in the kettle are taken out, and the residual moisture on the surface of the hanging pieces is absorbed with absorbent paper, and each piece is placed in the experimental storage bag; Step 4: Carry out nano-indentation test on cement stone corrosion area, and calculate the elastic modulus and Poisson's ratio of the test material through the load-displacement curve obtained by the indentation test. r From the load-displacement curve, E r is the elastic modulus test value; Step 5: Use the Mori-Tanaka mechanical model to achieve scale upgrade, and upgrade the elastic modulus and Poisson's ratio parameters at the micro / nano scale to the macro scale; Step 6: Clean and dry the corroded casing coupons, weigh the corroded coupons to obtain the mass G2, and calculate the corrosion rate; use the orthogonal test data of the casing coupons corrosion rate and the mathematical method of multiple regression to establish the corrosion rate of the casing pipe under the influence of temperature and CO2 partial pressure over time: V cor =Y·a·t b (9) In the formula, a and b are the corrosion temperature T and CO2 molar concentration C. (CO2) Factor function; Calculate the residual strength of uniform corrosion, for wall thickness δ, yield strength σ y The column, after corrosion time t: Remaining wall thickness of the pipe, i.e. size: δ t =δ-v t t(10) Residual tensile strength of pipe string: T o =πσ y [R 2 -(r+v t t) 2 ] / 4 (11) Residual internal pressure resistance of pipe string: p bo =2σ y (δ-v t t) / R (12) Residual collapse strength of pipe string: p co =2σ y [R / (δ-v t t)-1] / [R / (δ-v t t)] 2 (13) Where: T o is the residual tensile strength of the pipe string, kN; P bo is the residual internal pressure strength of the pipe string, MPa; P co is the residual collapse strength of the pipe string, MPa; t is the corrosion time, a; σ y is the yield strength of the pipe, MPa; R is the original outer diameter of the pipe, mm; r is the original inner diameter of the pipe, mm; δ is the original wall thickness of the pipe, mm; v t is the corrosion rate, mm / a; Step 7: Use the mathematical method of multiple regression to establish mathematical models of the changes of cement paste elastic modulus and Poisson's ratio with corrosion time under the influence of temperature and CO2 partial pressure factors; Step 8: Considering the phenomenon that CO2 corrodes cement stone to produce a corrosion layer, a mechanical model of the casing-cement stone non-corrosion layer-cement stone corrosion layer-stratum combination is established. The outside of the casing is the cement stone non-corrosion layer, and the outside of the cement stone non-corrosion layer is the cement stone corrosion layer. The casing, cement stone non-corrosion layer and cement stone corrosion layer are in the stratum. Step 9: Based on the numerical simulation results, the failure mode of wellbore integrity is determined. When the tangential stress on the cement sheath is greater than its tensile strength, the cement sheath undergoes tensile failure. When the equivalent stress on the cement sheath is greater than its compressive strength, the cement sheath fails. The tensile failure of cement paste depends on the circumferential stress state of the cement sheath, and the failure criterion is shown in formula (16). The compressive failure of cement paste depends on the radial stress state of the cement sheath, and the failure criterion is shown in formula (17). Based on the distortion energy theory, i.e., the fourth strength theory, the yield failure criteria of cement sheath and casing are shown in formulas (18) and (19). According to the three determination methods, the wellbore integrity failure forms are divided into cement sheath tensile failure, cement sheath compression failure, cement sheath yield failure, and casing yield failure. s θ ≥s t (16) s r ≥s c (17) s M ≤σ s (18) Where: t —Tensile strength of cement sheath, MPa; σ s — allowable stress of material determined by tensile test, MPa; σ M —Equivalent stress, MPa.

2. The method for evaluating wellbore integrity considering the changes in casing size and cement sheath performance after CO2 corrosion according to claim 1, characterized in that: The step 1 is specifically as follows: the indoor test adopts a multi-factor orthogonal test method, and determines the influencing factors based on the data provided on site, including temperature, CO2 partial pressure, formation water Cl - concentration and flow rate, an orthogonal matrix was established, and a total of N tests were conducted; the materials used in the test were casing pipes and cement ash provided on site in the oil field; the cement stone was prepared in accordance with GB / T19139-2012 Test Method for Oil Well Cement, and the cement stone sample was taken out after curing for 7 days, cleaned and sealed in anhydrous ethanol for standby use; the casing pipe was obtained by turning and milling, and the casing hanging piece was gradually polished with 200-1000# emery paper to achieve a mirror state, and then cleaned with deionized water and anhydrous alcohol in turn, and placed in a vacuum drying oven for standby use.

3. The method for evaluating wellbore integrity considering the changes in casing size and cement sheath performance after CO2 corrosion according to claim 2, characterized in that: The second step is specifically as follows: before the CO2 dynamic corrosion is carried out, the initial mechanical parameters of the standby cement stone are measured by a uniaxial tension and compression testing machine, and the initial mechanical parameters include compressive strength, elastic modulus, and Poisson's ratio; the casing hanging piece is weighed by a 0.1 mg electronic balance to obtain an initial mass of G1; the prepared cement stone and the weighed casing hanging piece are placed in the CO2 dynamic corrosion instrument, and the water content is calculated according to the liquid-gas ratio of the on-site produced gas, and the prepared Cl-containing - Formation water; the CO2 dynamic corrosion instrument is heated according to the preset temperature and pressure, CO2 is injected and the air in the kettle is removed for 5 minutes, CO2 gas with different partial pressures is injected, and the fluid flow rate controller in the kettle is turned on. The corrosion experiments are carried out for 3d, 5d, 7d, and 15d according to the preset corrosion time.

4. The method for evaluating wellbore integrity considering the changes in casing size and cement sheath performance after CO2 corrosion according to claim 3 is characterized in that: The step 4 is specifically as follows: using the G200X micro-nanomechanical testing platform to carry out nano-indentation experiments in cement stone corrosion areas, the radius of the calibrated Berkovich diamond indenter is less than 20nm, and the effective indentation depth is greater than 30μm; in the standard indentation test mode, a constant indentation strain rate of 0.05s is used during the loading process -1 The load-holding stage lasts for 60 seconds, and the rate of the unloading stage is kept the same as the indentation rate of the loading stage. The typical load-displacement curve obtained by the indentation test is used to calculate the elastic modulus and Poisson's ratio of the test material according to the Oliver-Pharr method, according to formula (1); E r Obtained from the load-displacement curve, according to formulas (2) and (3): Where: E—elastic modulus of the test material, GPa; v—Poisson’s ratio of the test material, dimensionless; E r —Elastic modulus test value, GPa; E i —Elastic modulus of the indenter, which is 1411 GPa; v i —Poisson’s ratio of the indenter, dimensionless, valued at 0.07; the elastic modulus test value is a comprehensive reflection of the elastic modulus of the indenter and the test material; S—contact stiffness, mN / nm, equal to the slope of the initial unloading curve; β—indenter shape correlation coefficient, dimensionless, Berkovich indenter is 1.034; A—indenter contact area, nm 2 , determined by pressure head calibration; P—load, mN; h—pressure depth, nm; h max —Maximum penetration depth of loading section, nm.

5. The method for evaluating wellbore integrity considering the changes in casing size and cement sheath performance after CO2 corrosion according to claim 4 is characterized in that: The mechanical model in step 5 is as follows: Among them, K hom —Shear modulus, unit: Pa; f r —Volume fraction of different mineral particles, unit: %, r = 0, 1, 2; f s —Volume fraction of s phase, unit: %, s=0, 1; k r —Volume modulus of different mineral particles, unit: Pa; k s —The proportion of clay minerals, unit: %; μ0 is the equivalent shear modulus of low-strength minerals, unit: Pa; G hom —Bulk modulus, unit: Pa; μ r —Shear modulus of different mineral particles, unit: Pa; k0—Equivalent bulk modulus of low-strength minerals, unit: Pa; μ s —Shear modulus of clay minerals, unit: Pa; E hom —Young's modulus after scale upgrade, unit: Pa; ν hom —Dimensionless Poisson’s ratio after scaling.

Citation Information

Patent Citations

  • Rock strength acquisition method based on nanoindentation testing

    CN112268825A

  • Alignment of responses for thickness estimations in a corrosion detection tool

    US20190086321A1